VARIASI LEKSIKAL DALAM SINKRETISME BUDAYA JUM’AT KLIWONAN DI LINGKUNGAN KERABAT HB VII DI DAERAH ISTIMEWA YOGYAKARTA - Siti MUKMINATUN (LPPM UNY, 2010)
This research aims at describing (1) types of lexical variation used by HB VII’s relatives and kanca pethak in the event of Jum’at Kliwonan, (2) the relationship between lexical variation and palace culture, (3) forms of lexical variation used by HB VII’s relatives and kanca pethak, and (4) conservation efforts of cultural syncretism in terms of lexical variation as a guide among the users of language in society. This research was based on field survey and employed descriptive-qualitative method. The data of this research were words and phrases uttered by HB VII’s relatives and kanca pethak in the event of Jum’at Kliwonan. The result of the research shows that there are 6 types of lexical variation based on the domains which cover them, namely ritual, friendship, social stratification, role relationship, trading, and general. In this event HB VII’s relatives and kanca pethak always use high variety of Javanese language. This variation reflects the social stratification in palace culture. The third result is that the forms of lexical variation are dominated by words, followed by compounds and clipping. The fourth shows that there are many efforts done by the group in the preservation of the event of Jum’at Kliwonan, namely by documenting the rules of the event, broadening the territory, and involving the youth in the event